2021
DOI: 10.1016/j.jhep.2020.09.013
|View full text |Cite
|
Sign up to set email alerts
|

A global investment framework for the elimination of hepatitis B

Abstract: Background and Aims More than 292 million people are living with hepatitis B worldwide and are at risk of death from liver cirrhosis and liver cancer. The World Health Organization (WHO) has set global targets for the elimination of viral hepatitis as a public health threat by 2030. However, current levels of global investment in viral hepatitis elimination programmes are insufficient to achieve these goals. Methods To catalyse political commitment and to encourage dome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 64 publications
0
76
0
Order By: Relevance
“…HCC-related mortality has steadily increased and almost tripled in the United States since the 1980s, where it is the fastest rising cause of cancer-related deaths with more than 39,000 cases and 29,000 deaths in 2018 [ 5 ]. Importantly, according to World Health Organization estimates, globally, more than one million patients will die from liver cancer in 2030 [ 6 ]. These data underscore the magnitude of the HCC-associated disease burden, which, despite the advances made in its surveillance and diagnosis, is still often diagnosed at advanced stages, precluding timely and eventually curative therapeutic intervention resulting in poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…HCC-related mortality has steadily increased and almost tripled in the United States since the 1980s, where it is the fastest rising cause of cancer-related deaths with more than 39,000 cases and 29,000 deaths in 2018 [ 5 ]. Importantly, according to World Health Organization estimates, globally, more than one million patients will die from liver cancer in 2030 [ 6 ]. These data underscore the magnitude of the HCC-associated disease burden, which, despite the advances made in its surveillance and diagnosis, is still often diagnosed at advanced stages, precluding timely and eventually curative therapeutic intervention resulting in poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis B virus (HBV) infections remain a significant global public health problem [ 1 ]. In 2017, the World Health Organization (WHO) reported that 257 million people suffer from chronic HBV infection, and nearly 887,000 deaths were registered worldwide due to the hepatitis B virus pathogen [ 2 ]. In general, there are two different strategies used in the treatment of HBV infection: the short-term therapy based on immune-modulators, such as standard or PEGylated interferon-α; and the long-term regime composed of the nucleosides and nucleotides analogues, such as tenofovir, lamivudine, entecavir, telbivudine, etc.…”
Section: Introductionmentioning
confidence: 99%
“…To do so, a 90% reduction in HBV infection incidence (ie 0.1% prevalence of HBsAg in under‐five‐year‐olds) and a 65% reduction in HBV mortality need to be achieved by 2030 5 . Our study is particularly relevant, as local‐level epidemiological data are needed to provide information not only on the HBV epidemic and driving factors for transmission, but also on the progress being made in achieving the GHSS elimination goal 28 …”
Section: Discussionmentioning
confidence: 99%